Assessment of human norovirus inhibition in cabbage kimchi by electron beam irradiation using RT‐qPCR combined with immunomagnetic separation. Issue 2 (7th January 2021) - Jeong, Myeong‐In; Lee, Eun Ji; Park, Shin Young; Kim, Mi Rae; Park, Sa Reum; Moon, Yoah; Choi, Changsun; Ha, Ji‐Hyoung; Ha, Sang‐Do
Abstract : Abstract: Cabbage Kimchi, a traditional Korean fermented food, has occasionally been related to acute gastroenteritis caused by human norovirus (HuNoV). The present study examined the inhibitory effects of electron beam (e‐beam) irradiation (1, 3, 5, 7, and 10 kGy) on HuNoV GII.4 in suspension or cabbage Kimchi using reverse transcription quantitative polymerase chain reaction combined with immunomagnetic separation (IMS/RT‐qPCR). In addition, physicochemical and sensorial analyses were conducted to assess any change in the quality of cabbage Kimchi following e‐beam irradiation. Following e‐beam irradiation at 1 to 10 kGy, HuNoV significantly decreased to 0.28 to 2.08 log10 copy number/mL in suspension ( P < 0.05). HuNoV levels in cabbage Kimchi were also significantly reduced to 0.26 to 1.57 log10 copy number/mL following irradiation with 1 to 10 kGy ( P < 0.05) compared to positive control (6.0 log10 copy number/mL). The D ‐values for 1 log10 reduction (90% inhibition) of HuNoV in suspension and cabbage Kimchi were 4.94 and 6.96 kGy of e‐beam, respectively. The pH and acidity in the irradiated cabbage Kimchi were 4.41 to 4.58 and 0.61% to 0.71%, respectively, indicating that e‐beam did not affect the optimal pH or acidity. Although a slight increase of greenness was observed in the leaf portion of cabbage Kimchi irradiated with 7 to 10 kGy of e‐beam, this color change was minimal and went undetected by panelists in the sensorial evaluation. The five properties of sensorial quality assessed were no different in the irradiated Kimchi sample compared with the control sample (nonirradiated cabbage Kimchi). Therefore, this study suggests that ≥6.96 kGy of e‐beam could be applied in the cabbage Kimchi industry to obtain >90% of HuNoV without affecting the quality. Practical Application: As the most representative food in Korea, Kimchi needs the sanitation technology that can inhibit viral infection. Our findings suggest that e‐beam irradiation can be used to reduce HuNoV effectively in Kimchi without changes in sensorial quality.